Von Tischlern und ihren Arbeiten im Zeitalter des Absolutismus: II: Kunstlandschaften im Norden, Süden und Westen - Bohr, Michael (2021)
The multi-volume study on Austrian baroque furniture is based on sacred interiors. It contains information on the development of sacred furniture, descriptions of the furniture sets and an analysis of their stylistic characteristics. In addition, it investigates cultural-, economic- and socio-historical issues. Volume I: https://e-book.fwf.ac.at/o:1112.